Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations bruise or a graze, to enter the body and set up mischief. A clean skin is a safe skin. It is important to form a good habit of cleanliness whilst young enough to form habits easily. A clean mind and a clean body go together, and a feeling of self-respect follows this cleanliness of person. Dirty habits affect others, are unpleasant and unsocial, the mark of selfishness. Cleanliness is refinement, and everything that tends to outer nicety reacts favourably on mind and emotions. A clean person will instinctively prefer a clean environment and will be the man or woman who creates order and irradiates Beauty wherever he or she may be. Thus Cleanliness, the cult of soap and water, is a social virtue of great value. BEAUTIFUL HANDS It is not a bit necessary to live in the lap of luxury in order to have beautiful hands. Tennis and motoring are as apt to work the same havoc as washing-up and housework, if the hands do not receive proper care. And the means are so simple! All you want is a good nailbrush, a pot of cold cream or skin food and — common sense! [illustration] Hands were made to be useful, but that is no reason why they should not also be beautiful. They become dirty at times, but, thank goodness, they will wash! When you are on a dirty job and cannot wear gloves, cover the hands with a "dry" thick lather of soap, letting it get under the nails; or dig your nails into a cake of soap; then when you wash, soap and dirt will come away easily together. Short nails are more easy to keep clean and 5 177/5/8/4